Certain Properties of a Class of Close-to-Convex Functions Related to Conic Domains - Wasim Ul-Haq (Abstract and Applied Analysis, 2013)
We aim to define a new class of close-to-convex functions which is related to conic domains. Many interesting properties such as sufficiency criteria, inclusion results, and integral preserving properties are investigated here. Some interesting consequences of our results are also observed.